2016
DOI: 10.1080/10942912.2016.1168837
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition, enzyme inhibitory, and antioxidant activities of the ethanol extracts of selected wild edible plants consumed as vegetables in the Aegean region of Turkey

Abstract: Tepe (2017) Fatty acid composition, enzyme inhibitory, and antioxidant activities of the ethanol extracts of selected wild edible plants consumed as vegetables in the Aegean region of Turkey, International

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…Other fatty acids in these oils include linoleic, oleic, and palmitic acids as the next most prominent ones together with minor amounts of stearic and linolenic acids. While many individual publications reporting the fatty acid profiles of Apiaceae species agree with this assessment, other publications mention only the presence of oleic acid but not petroselinic acid, rather reporting high content of the former or polyunsaturated fatty acids or not distinguishing between various C18:1 fatty acids . The issue of not identifying petroselinic acid is likely due to the co‐elution of the methyl esters of petroselinic and oleic acids at virtually identical retention times during gas chromatographic analyses .…”
Section: Introductionmentioning
confidence: 92%
“…Other fatty acids in these oils include linoleic, oleic, and palmitic acids as the next most prominent ones together with minor amounts of stearic and linolenic acids. While many individual publications reporting the fatty acid profiles of Apiaceae species agree with this assessment, other publications mention only the presence of oleic acid but not petroselinic acid, rather reporting high content of the former or polyunsaturated fatty acids or not distinguishing between various C18:1 fatty acids . The issue of not identifying petroselinic acid is likely due to the co‐elution of the methyl esters of petroselinic and oleic acids at virtually identical retention times during gas chromatographic analyses .…”
Section: Introductionmentioning
confidence: 92%
“…8 Using similar methods, Sarikurkcu et al reported the TP and TF contents of ethanol extracts of E. cicutarium from Turkey to be 32.14 ± 1.18 mg gallic acid equivalents/g extract and 52.09 ± 0.45 mg rutin equivalents/g extract, respectively, while data of TP and TF in this study, as shown previously, are expressed as percentages of dry weight of plant material. 30 A reasonably high phenolic content in the examined Croatian populations is shown for the first time, which indicates their substantial antioxidant potential, and so it could be of benefit to explore their antioxidant activity and radical scavenging capacity in the future.…”
mentioning
confidence: 83%
“…By using several solvents and extraction procedures, there have been reports describing E. cicutarium as a source of phenolic compounds, 24 including phenolic acids and depsides, flavonoids, tannins (T), saponins, sugars, amino acids, saturated and unsaturated fatty acids, and vitamins K and C. 8,9,[25][26][27][28][29][30] Encouraged by the known ethnopharmacological data for E. cicutarium and its shown phytochemical potential, this research was designed to evaluate the phytochemical and micromorphological characteristics of wild growing populations of E. cicutarium, an insufficiently investigated native medicinal plant in the South East European flora.…”
mentioning
confidence: 99%
“…A literature search reveals that, besides studies targeting the chemically diverse essential oil composition, [10 -13] there are only few data regarding phytochemical analysis of different types of extracts and they indicate the presence of hydroxycinnamic acids, flavonoids, tannins, saponins, sugars, amino acids, fatty acids and vitamins. [3,4,8,13 -19] Sarikurkcu et al [18] reported contents of total phenolics, total flavonoids, total flavanols and total saponin content for ethanol extracts of E. cicutarium from Turkey. In physicochemical analyses conducted by Nikitina et al, [13] phenolic compounds were also found, including flavonoids, phenylpropanoids, condensed phenols and hydroxycinnamic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the diverse traditional use into account and, among others, the presence of polyphenolic constituents, it is not surprising that previous experimental studies showed data supporting antioxidant, antimicrobial, spasmogenic, interferonogenic, antiviral and antiproliferative activity. [1,8,12,14,18,19,[21][22][23][24] Although data regarding in vitro antioxidant activity of E. cicutarium can be found in literature, it still lacks a 'whole picture perspective' from a uniform experimental point of view, especially considering the variations in solvent choice and extract preparation conditions that make it rather difficult to compare data published so far. [14,18,19,24] To our best knowledge, most available literature data of antioxidant activity extracts of E. cicutarium are a result of testing activity of ethanol extracts.…”
Section: Introductionmentioning
confidence: 99%